Laparoscopic findings of congenital hepatic fibrosis: A case report and review of the published work. Issue 7 (17th July 2013) - Komatsu, Michiharu; Tanaka, Naoki; Shibata, So‐Ichirou; Kimura, Takefumi; Ichikawa, Yuki; Morita, Susumu; Joshita, Satoru; Nagaya, Tadanobu; Umemura, Takeji; Ichijo, Tetsuya; Matsumoto, Akihiro; Yoshizawa, Kaname; et al.
<x xml:space="preserve">Abstract</x> A 33‐year‐old man visited a hospital after vomiting blood. Emergent esophagogastroduodenoscopy revealed the presence of varices in the lower esophagus. The patient did not have a past history of alcohol consumption and was negative for hepatitis B and C viruses. He was referred to our hospital for closer examination. Portal hypertension was detected by conventional imaging modalities, but signs of liver cirrhosis, thrombosis, stenosis, malformation of the portal vein and bile duct abnormalities were not observed. We performed laparoscopy‐guided liver biopsy to examine the cause of portal hypertension. In addition to prominent development of collateral vessels on hepatic ligaments and the omenta, marbled whitish markings with black‐green spots were dispersed over the liver surface, but nodular formation and lymphatic vesicles were not found. Biopsied specimen demonstrated severe dense fibrosis in portal areas and von Meyenburg complexes (vMC). Based on these findings, the diagnosis of congenital hepatic fibrosis (CHF) was made. Post‐biopsy hemostasis was confirmed under laparoscopy and no major complications occurred after biopsy. We reviewed 11 cases of CHF which had undergone laparoscopy in Japan, including our case. Marbled whitish markings, black‐green spots and collateral vessels were seen in 11, five and seven cases, respectively. When we encounter the patients having portal hypertension of unknown etiology, laparoscopy‐guided liver biopsy should be considered as a safe and useful diagnostic procedure. Black‐green spots in marbled whitish markings, which reflect vMC in broad fibrotic areas, are laparoscopic characteristics of CHF.